2009
DOI: 10.1017/s0007114509274745
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake, physical activity and nutritional status in adults: the French nutrition and health survey (ENNS, 2006–2007)

Abstract: The French National Programme on Nutrition and Health (Programme national nutrition santé (PNNS)), the aim of which is to reduce nutritionrelated chronic diseases, necessitates monitoring of nutritional characteristics. Our objective was to describe dietary intake, physical activity and nutritional status in a national sample of adults, especially according to current French recommendations. The study is based on a cross-sectional population-based survey using a multistage sampling design (Etude nationale nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
131
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 44 publications
14
131
1
2
Order By: Relevance
“…Lastly, Mozaffarian et al (10) have even suggested that consuming PUFA in place of SFA reduces CHD events in randomized control trials. According to the nutritional recommendations of the French PNNS, our study confirmed the results of two other French studies in which subjects recruited through a media campaign had an unsatisfactory diet (35,36) . In our study, only 11?6 % had an F&V score corresponding to five servings per day.…”
Section: Discussionsupporting
confidence: 87%
“…Lastly, Mozaffarian et al (10) have even suggested that consuming PUFA in place of SFA reduces CHD events in randomized control trials. According to the nutritional recommendations of the French PNNS, our study confirmed the results of two other French studies in which subjects recruited through a media campaign had an unsatisfactory diet (35,36) . In our study, only 11?6 % had an F&V score corresponding to five servings per day.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with other studies on both general and lowincome populations (Cristofar and Basiotis, 1992;Dixon et al, 2001;Tarasuk, 2001), our findings also highlighted the fact that, the more severe the food insufficiency, the lower the consumption of meat, seafood and eggs, dairy products and, fruits and vegetables. Although food aid users generally had much lower consumption of these foods than the general French population (Castetbon et al, 2009), this observation underlines the fact that, irrespective of their common highly precarious situation, some food aid users considered themselves to be food sufficient. Various strategies may be used by individuals when confronted with the problem of food insufficiency, including dietary changes, food-seeking strategies and rationing strategies, such as skipping meals and skipping eating for entire days (Oldewage-Theron et al, 2006).…”
Section: 00mentioning
confidence: 76%
“…However, Radimer and Radimer showed that the four-part response to the Food Sufficiency Indicator fairly accurately estimates food insecurity (4) . Second, although the participation rate in the survey (63 %) is similar to that obtained in another similar French survey requiring home visits (68) , possible occurrence of a selection bias it cannot be excluded. Moreover, the study design excluded some population groups (e.g.…”
Section: Limitations and Strengthsmentioning
confidence: 64%